A novel mode of cytokinesis without cell-substratum adhesion - Risa Taira (Nature Portfolio, 2017)
Abstract Cytokinesis is a final step in cell division. Dictyostelium cells, a model organism for the study of cytokinesis, have multiple modes, denoted cytokinesis A, B, C, and D. All these modes have been mainly investigated using cells adhering to the substratum although they can grow in shaking suspension culture. Here, we observed how cells divide without adhering to the substratum using a new non-adhesive material. These detached cells formed the cleavage furrow but eventually failed in the final abscission. Thus, the cells cannot divide without adhesion, suggesting that they cannot divide only through the conventional cytokinesis A. However, in a long-term culture, the detached cells adhered each other to form multicellular aggregates and divided properly in these aggregates. Myosin II-null cells also formed such aggregates but could not divide in the aggregates. Several lines of experiments using mutant cells showed that the process of cytokinesis in multicellular aggregates is a novel mode utilizing a confined space in the aggregate in a myosin II-dependent manner. These results shed light on a poorly characterized mechanism of cytokinesis in multicellular spheroids or tissues. We propose to redefine and classify multiple modes of cytokinesis.